A selection of early Welsh saga poems - Rowland, Jenny, 1950- (Library of medieval Welsh literature., 2014)
"The saga englynion are among the most appealing medieval Welsh poems. Despite some difficulties, their style is generally direct and their contents interesting to modern readers. In these poems the anonymous poets speak as characters from story. The full narrative setting has been lost, but enough can be reconstructed to appreciate the poetry. This selection includes dramatic dialogues and monologues exploring the acceptable limits of heroism. The old warrior, Llywarch Hen, mourns his sons' death in battle and his lonely old age full of regrets. Heledd, the only major female character in the saga poetry, laments the loss of her family and her country to the invading English. A Selection of Early Welsh Saga Poems, the fifth volume of the Library of Medieval Welsh Literature Series, presents edited texts from the main manuscripts. The introduction offers a guide to interpretation, dating, and metrics, while a full glossary and explanatory notes make these poems readily accessible to the reader."--